PENGARUH TINGKAT SUKU BUNGA KREDIT MODAL KERJA DAN DAYA BELI MASYARAKAT TERHADAP VOLUME PENYALURAN KREDIT MODAL KERJA PADA PT. BPR MITRA KANAKA SENTOSA - Dian Ardiyanti, - (2010)
The Effect Of The Interest Rate Of Working Capital Loan and Purchasing Power toward The Distribution Volume Of Working Capital Loan Of PT.BPR Mitra Kanaka Sentosa. Dian Ardiyanti (044699) Guided and Supervised by : 1. Silviana Agustami, M.Si,Ak 2. Hj. Alfira Sofia, ST,MM As a financial intermediation institution, PT. BPR Mitra Kanaka Sentosa has undergone their role function as a bank which is fund gathering from society and distribute it to society as well. One of fund distribution that has been done is giving credits to society along with the interests. One of loan given is working capital loan that needed by society in recent, especially Small and Medium Industry. This research is objected to observe on how interest rate of working capital loan development, purchasing power, working capital loan distribution volume, and to what extend the interest rate of working capital loan and purchasing power influence working capital loan of PT. BPR MKS's distribution volume. Descriptive and verificative methode are used in this research, while correlational design is used to know the relation and effect of variable and other variables. Meanwhile, the data gathering technique used is interest rate of working capital loan, purchasing power and the distribution volume of working capital loan documents during 17 months from January 2008 to May 2009 in purposive sampling technique. From hypotical test experiment result, knew that partial correlation coeficient between the rate interest of working capital loan and the distribution volume of working capital loan is 0.301 which means that they have the low correlation. The purchasing power and distribution volume of working capital loan is 0.507, which means that have a middle correlation. The corelation coeficient between interest rate of working capital loan and purchasing power in the manner of simulty with distribution volume of working capital loan is 0.510 which means that have a middle correlation and determination coeficient is 0.260 or 26%, which means that the effect of interest rate of working capital loan and purchasing power toward distribution volume of working capital loan is 26% but another 74% are effected by other variables.